A fatal case of pulmonary infection with Lagochilascaris sp., probably Lagochilascaris minor Leiper, 1909 - Moraes, Mário A. P.; Arnaud, Maria Vanda Catão; Macedo, Roberto Cavalleiro de; Anglada, Antônio Ernesto (Revista do Instituto de Medicina Tropical de São Paulo, 1985)
A fatal case of pulmonary infection with Lagochilascaris sp. probably Lagochilascaris minor is presented. A 18-year-old girl from Curralinho State of Para developed a severe pneumonitis of unknown origin, and died less than three months after the onset of the illness, She was admitted to the Hospital, in Belem-Pará, on 16 June 1983, with fever, productive cough, dyspnea and, eventually, cyanosis. At that time, she had been sick for at least four or five weeks. A chest X-ray film taken shortly after admission disclosed extensive bilateral infiltrates, predominantly on the right lung. Acid-fast bacilli and fungi, however, could not be demonstrated in the sputum. The leucocyte count was low (3.900), with 60% neutrophils and 40% lymphocytes. In spite of several therapeutic schedules (no definite cause for the disease could be found) the patient's condition rapidly deteriorated. She persisted with fever, cough, expectoration of thick sputum, dyspnea and cyanosis, but other symptoms also came forth: hoarseness, fatigue, weight loss and labored breathing. On 13 July she developed respiratory insufficiency and died. At autopsy, the lungs appeared distended with numerous areas of consolidation; the cut surface, when exposed, revealed disseminated foci, both nodular and diffuse, of granulomatous and exsudative inflammation. Microscopically, sections of eggs and round worms were found in the preparations, always surrounded by granulomas or large areas of necrotic tissue. The worms were recognized as evolutive stages larvae, adult males and a gravid female of a nematode belonging to the genus Lagochilascaris, probably Lagochilascaris minor. The identification was based, mainly, on the aspect of the eggs, which exhibited the irregular-shaped, saucerlike depressions or pits, characteristic of the genus. The female worm had lateral alae and the uterus full with similar eggs. In all 25 cases of human lagochilascariasis so far described, the location of the lesions was in the region of neck, ear, mastoid process, orbit, paranasal sinuses and retropharyngeal tissues. For the first time, the present case, a member of the genus Lagochilascaris is referred to in a different site of the host. Besides that, the finding of eggs, larvae and adult worms in the lung tissues strongly suggests the existence of a pulmonary cycle in human lagochilascariasis.